Inhibition of IL-6 in the LCWE Mouse Model of Kawasaki Disease Inhibits Acute Phase Reactant Serum Amyloid A but Fails to Attenuate Vasculitis - Porritt, Rebecca A.; Chase Huizar, Carol; Dick, Edward J.; Kumar, Shyamesh; Escalona, Renee; Gomez, Angela C.; Marek-Iannucci, Stefani; Noval Rivas, Magali; Patterson, Jean; Forsthuber, Thomas G.; Arditi, Moshe; Gorelik, Mark (Frontiers in Immunology, 2021)
Objective: Kawasaki disease (KD) is the most common cause of acquired pediatric heart disease in the developed world. 10% of KD patients are resistant to front-line therapy, and no interventions exist to address secondary complications such as myocardial fibrosis. We sought to identify proteins and pathways associated with disease and anti-IL-1 treatment in a mouse model of KD. Methods: Vasculitis was induced via Lactobacillus casei cell wall extract (LCWE) injection in 5-week-old male mice. Groups of mice were injected with LCWE alone, LCWE and IL-1 receptor antagonist anakinra, or saline for controls. Upper heart tissue was assessed by quantitative mass spectrometry analysis. Expression and activation of STAT3 was assessed by immunohistochemistry, immunofluorescence and Western blot, and IL-6 expression by RNA-seq and ELISA. A STAT3 small molecular inhibitor and anti-IL-6R antibody were used to evaluate the role of STAT3 and IL-6 in disease development. Results: STAT3 was highly expressed and phosphorylated in cardiac tissue of LCWE-injected mice, and reduced following anakinra treatment. Il6 and Stat3 gene expression was enhanced in abdominal aorta of LCWE-injected mice and reduced with Anakinra treatment. IL-6 serum levels were enhanced in LCWE-injected mice and normalized by anakinra. However, neither inhibition of STAT3 nor blockade of IL-6 altered disease development. Conclusion: Proteomic analysis of cardiac tissues demonstrates differential protein expression between KD-like, control and treated cardiac tissue. STAT3 and IL-6 were highly upregulated with LCWE and normalized by anakinra treatment. However, both STAT3 and IL-6 were dispensable for disease development indicating they may be bystanders of inflammation.